1998
DOI: 10.1046/j.1365-2249.1998.00606.x
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic thymic epithelial cells of human thymoma support T cell development from CD4−CD8− cells to CD4+CD8+ cellsin vitro

Abstract: Human thymoma is a thymic epithelial cell tumour which often contains a large number of immature T cells and is frequently associated with autoimmune diseases. Since thymic epithelial cells play key roles in the development and selection of T cells in the normal thymus, we hypothesized that the neoplastic thymic epithelial cells of thymoma may support T cell differentiation in the tumour. We characterized CD4-CD8- cells in thymoma and applied an in vitro reconstitution culture system using the CD4-CD8- cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…In fact, a study that utilized an in vitro culture system showed that neoplastic epithelial cells from thymomas induced differentiation of CD4 − CD8 − T-cell precursors to CD4 + CD8 + double-positive T cells. 19 Several types of malignant lymphomas also have the CD4 + CD8 + double-positive phenotype, although those lymphoma neoplastic cells are quite different from CD4 + CD8 + double-positive T cells found in thymomas. Lymphoma neoplastic cells with the CD4 + CD8 + phenotype have a certain level of CD3 expression, indicating that neoplastic lymphoma cells emerged from a T cell at a particular stage of T-cell differentiation in the thymus.…”
Section: T-cell Development In Thymomamentioning
confidence: 99%
“…In fact, a study that utilized an in vitro culture system showed that neoplastic epithelial cells from thymomas induced differentiation of CD4 − CD8 − T-cell precursors to CD4 + CD8 + double-positive T cells. 19 Several types of malignant lymphomas also have the CD4 + CD8 + double-positive phenotype, although those lymphoma neoplastic cells are quite different from CD4 + CD8 + double-positive T cells found in thymomas. Lymphoma neoplastic cells with the CD4 + CD8 + phenotype have a certain level of CD3 expression, indicating that neoplastic lymphoma cells emerged from a T cell at a particular stage of T-cell differentiation in the thymus.…”
Section: T-cell Development In Thymomamentioning
confidence: 99%
“…Isolation of thymoma-derived neoplastic epithelial cells TECs were obtained from fresh thymomas, as previously described (Inoue et al 1998;Inoue et al 1999). Fresh tissue from the eight patients was minced and cultured for 5 days in the presence of 1.35 mM 2-deoxyguanosine (Sigma, St. Louis, Mo., USA) in complete medium (RPMI 1640 supplemented with 10% FCS, 2 mM glutamine, 5 lM 2-mercaptoethanol, and antibiotics) to remove thymocytes.…”
Section: Patients and Samplesmentioning
confidence: 99%
“…To determine the percentage of positively stained cells, the range was set as closely as possible so that 99% of the control stained cells fell within the negative region. The expression level of each molecule was also evaluated in terms of the D-value, as in the non-parametric Kolmogorov-Smirnov test, using Cell Quest (Inoue et al 1998;Kadota et al 2000;Young 1977). The results are shown as the mean percentage±SD.…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
“…Interestingly, a considerable portion of these thymomaassociated lymphocytes are CD4 ϩ CD8 ϩ double positive, a phenotype of the cortical thymocytes [5][6][7][8][9], suggesting that thymoma neoplastic epithelial cells retain function as the thymic epithelium to induce T cell development. Actually, the neoplastic epithelial cells derived from thymomas have been shown to be capable of inducing CD4 ϩ CD8 ϩ cells from CD3 -CD4 -CD8 -CD34 ϩ T cell precursors in an in vitro culture [10]. Additionally, another observation that CD4 ϩ CD8 ϩ double positive lymphocytes exist even in the thymoma metastatic sites [11] strongly suggests that T cell development takes place even in a thymoma neoplastic environment.…”
Section: Introductionmentioning
confidence: 99%